PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VI SEKOLAH DASAR - Dwi Mardalena (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
This research is motivated by the results of student learning science VI low grade of primary school 9 Duri Barat with an average value of 67.14. Therefore, the researchers provide learning alternatives to the application by implementing role playing model in class VI SD Negeri 9 Duri Barat. This research aims to improve student learning outcomes VI Elementary School science class 9 Duri Barat Application by implementing role playing model. This research is a form of classroom action research (PTK) with 2 cycles. Based on research data anlisis after applying by implementing role playing model, the average percentage of the activity of teachers in the first cycle of 62.5% increased to 85.25% in the second cycle. The average percentage of student activity also increased 50% in the first cycle increased to 83.3% in the second cycle. Student learning outcomes in basic score with an average of 67.14 with 50% completion percentage of classes and the first cycle increased with an average value of 75.17 class with an increasing percentage of learning outcomes of 11.96% and the percentage of students who complete 57, 14%. Then the average value silus class II increased to 87.85 with the percentage increase learning outcomes by 30.84% and the percentage of students who completed was 85.71%, after the implementation by implementing role playing model. These results indicate that the implementation by implementing role playing model can improve student learning outcomes Elementary School science class VI SD Negeri 9 Duri Barat.